2018
DOI: 10.1177/0954411918789450
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of variables used to assess clinically acceptable alignment of unilateral transtibial amputees in the literature

Abstract: Prosthetic alignment is a subjective concept which lacks reliability. The outcome responsiveness to prosthetic alignment quality could help to improve subjective and instrument assisted prosthetic alignment. This study was aimed to review variables used to assess clinically acceptable alignment in the literature. The search was done in some databases including: Google Scholar, PubMed, EBSCO, EMBASE, ISI Web of Knowledge and Scopus. The first selection criterion was based on abstracts and titles to address the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…In the prosthetics field, questionnaires have also been used to assess prostheses, mobility outcomes, and quality of life, but none have been designed specifically for assessing the quality of prosthetic alignment. Therefore, various research studies have tried to find more quantitative techniques 11 and optimization criteria for prosthetic alignment 12 that can assist and guide the prosthetist to obtaining an acceptable prosthetic alignment because it facilitates stable ambulation, enhance comfort, produce aesthetic gait appearance, and lower the energy cost of walking. 13 Despite advances in prosthetic technology, amputees, prosthetists, researchers, and manufacturers have insisted that the quality of prosthetic alignment requires improvements in which alignment needs improved tools for prosthetists, improved communication between amputees and prosthetists, as well as knowledge of alignment-related outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the prosthetics field, questionnaires have also been used to assess prostheses, mobility outcomes, and quality of life, but none have been designed specifically for assessing the quality of prosthetic alignment. Therefore, various research studies have tried to find more quantitative techniques 11 and optimization criteria for prosthetic alignment 12 that can assist and guide the prosthetist to obtaining an acceptable prosthetic alignment because it facilitates stable ambulation, enhance comfort, produce aesthetic gait appearance, and lower the energy cost of walking. 13 Despite advances in prosthetic technology, amputees, prosthetists, researchers, and manufacturers have insisted that the quality of prosthetic alignment requires improvements in which alignment needs improved tools for prosthetists, improved communication between amputees and prosthetists, as well as knowledge of alignment-related outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…16 There are a few systematic reviews that have developed approaches to evaluate existing measurement parameters, or variables used to assess clinically acceptable alignment, which is primarily focused on studies that examine the effect of changes in TT prosthetic alignment on the total body, gait symmetry, electromyography and oxygen consumption, TT socket pressure changes, spatiotemporal, kinematic, as well as kinetic gait parameters. [11][12][13]17,18 In this systematic review, as the primary research question, the current literature on TT prosthetic alignment will be examined to scope the qualitative and quantitative methods that were intended to assist prosthetists in achieving an acceptable TT prosthetic alignment. This study is also aimed to shed the light on the reported TT prosthetic alignment instruments/devices and their clinical feasibility.…”
Section: Introductionmentioning
confidence: 99%
“…6 In the clinic, it is usually based on gait observations of professionals (prosthetists, physicians, and physical therapists) and the experiences of the patient. [7][8][9] The goal is to create a comfortable, natural gait pattern, with the least possible asymmetry and compensation in the contralateral leg and core. 9 The prosthetic alignment, especially the "fine-tuning" of the prosthesis based on the patient's needs, is an ongoing process during subacute rehabilitation because the stump often undergoes several changes during this period and the patient develops a better understanding of adequate alignment.…”
Section: Introductionmentioning
confidence: 99%
“…4 Comfort and function of the prosthesis critically depend on the socket alignment and fit. 46…”
Section: Introductionmentioning
confidence: 99%